2010
DOI: 10.1111/j.1365-2761.2010.01147.x
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology of culture‐associated skin erosions and papillary hyperplasia of Atlantic halibut, Hippoglossus hippoglossus (L.)

Abstract: Atlantic halibut, Hippoglossus hippoglossus (L.), that were cultured in tanks with a smooth bottom (gel-coated fibreglass) substrate developed papillary hyperplasia and skin erosions on the blind (ventral) side. No viruses, bacteria or parasites were observed in any sections of affected skin. Comparison of microscopic pathology with that of skin from normal, wild-caught halibut showed severe epidermal proliferation with foci of severe mucous cell hyperplasia. Both epidermal thickness and mucous cell density we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Bereiter‐Hahn (1986) reported that the main factor controlling the cell movement seems to be contact inhibition of motility or contact paralysis, that is, as soon as advancing margins of epidermal sheet come in contact, migration ceases. Quilhac and Sire (1999) has also reported piling up of the epithelial cells after the closure of the wound to form an epidermal fold (= epidermal ridge, present investigation) in the fish H. bimaculatus and suggested that the contact inhibition does not occur immediately. Nevertheless, Silva et al (2004), in N. coriiceps , did not observe epidermal ridge and reported immediate fusion of the migrating epidermis after the contact of the opposing fronts.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Bereiter‐Hahn (1986) reported that the main factor controlling the cell movement seems to be contact inhibition of motility or contact paralysis, that is, as soon as advancing margins of epidermal sheet come in contact, migration ceases. Quilhac and Sire (1999) has also reported piling up of the epithelial cells after the closure of the wound to form an epidermal fold (= epidermal ridge, present investigation) in the fish H. bimaculatus and suggested that the contact inhibition does not occur immediately. Nevertheless, Silva et al (2004), in N. coriiceps , did not observe epidermal ridge and reported immediate fusion of the migrating epidermis after the contact of the opposing fronts.…”
Section: Discussionsupporting
confidence: 58%
“…In L. rohita , the epidermal ridge is prominent up to 12 h and thereafter it gradually disappears. Quilhac and Sire (1999) reported that such a fold persists for at least 18 h in H. bimaculatus .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Mucous cell exhaustion with a reduced number of active cells is often seen as a response to injury (Ottesen et al 2010, Ozerov et al 2010. Contrarily, club cells respond to parasite injuries with an increase in cell size and density.…”
Section: Discussionmentioning
confidence: 99%
“…The epidermal tissue of fish is often the primary barrier, to pathogens in the environment (Singh and Mittal 1990, Iger et al 1994, Rakers et al 2010, Ottesen et al 2010. The cell-mediated innate mechanisms of epidermal tissues include specialized cells such as macrophages, granulocytes, natural killer cells, and also physical barriers such as mucous layers and skin epithelial tissue lines (Jones 2001, Aoki et al 2008.…”
Section: Introductionmentioning
confidence: 99%